Morphological and Molecular Evidence for Two New Species within Russula Subgenus Brevipes from China - Jie Song; Haijiao Li; Shijun Wu; Qianqian Chen; Guang Yang; Jinyun Zhang; Junfeng Liang; Bin Chen (Diversity, 2022)
Two new Russula species, R. subbrevipes and R. callainomarginis, from China are described based on morphological and molecular characteristics. Russula subbrevipes has thus far only been found in southwestern China at altitudes of higher than 3400 m and is characterized by a yellow ochre pileal surface, glabrous or tomentose stipe, fruity odor, subglobose to ellipsoid basidiospores, isolated or partially connected warts and pleurocystidia with a cap appendage. Russula callainomarginis is characterized by a cream to white pileus, light turquoise lamellae margin, spongy stipe, light turquoise zone on the top of the stipe, pungent odor, globose to ellipsoid basidiospores and dominant isolated warts. The phylogenetic tree of Russula was constructed with multi-gene sequences, including the internal transcribed spacer regions (ITS), the ribosomal large subunit (nrLSU), the small subunit of the mitochondrial rRNA gene (mtSSU) and the second largest subunit of RNA polymerase II (RPB2). The results show that both R. subbrevipes and R. callainomarginis represent new lineages in Russula subg. Brevipes. Description and illustration of the two new species are presented.